317 GHz InAlGaN/GaN HEMTs with extremely low on‐resistance. Issue 5 (29th January 2013) - Lee, Dong Seup; Laboutin, Oleg; Cao, Yu; Johnson, Wayne; Beam, Edward; Ketterson, Andrew; Schuette, Michael; Saunier, Paul; Kopp, David; Fay, Patrick; Palacios, Tomás; Krishna, Sanjay; et al.
Abstract This paper reports depletion‐mode In0.13Al0.83Ga0.04N/GaN high electron mobility transistors (HEMTs) on a SiC substrate with a record current gain cutoff frequency (fT) of 317 GHz. Thanks to the combination of high electron mobility, regrown n+ InGaN/GaN ohmic contacts and scaled source‐to‐drain distance, the devices have an very low on‐resistance of 0.4 Ω·mm. This very low resistance enables a significant reduction of the transistor parasitic delay and devices with a peak fT of 317 GHz have been demonstrated for a 26 nm gate length. The device performance is limited by a relatively thick top barrier which causes serious short‐channel effects (SCEs) in the devices with gate length below 50 nm. It is expected that a suppression of the SCEs will render further improvements in frequency performance in future devices. (© 2013 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)